2014
DOI: 10.1002/pon.3699
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive coping style (monitoring and blunting) and the need for information, information satisfaction and shared decision making among patients with haematological malignancies

Abstract: Among patients with haematological malignancies, coping style is related to a need for information, information satisfaction, and involvement in treatment decision-making. Therefore, it is important for health care professionals to be aware of individual differences in cognitive coping style.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 24 publications
4
36
0
Order By: Relevance
“…() and Rood, van Zuuren, Stam, van der Ploeg, Huijgens, et al. () appeared to use the same sample. While all qualitative papers included only haematological cancer patients, four of the 13 papers with quantitative data included participants with other cancers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…() and Rood, van Zuuren, Stam, van der Ploeg, Huijgens, et al. () appeared to use the same sample. While all qualitative papers included only haematological cancer patients, four of the 13 papers with quantitative data included participants with other cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative sample sizes ranged from 31 to 3,080 and qualitative samples ranged from 11 to 54. Collectively the quantitative studies included 6,575 participants (counting the sample reported by Rood, van Zuuren, Stam, van der Ploeg, et al., ; Rood, van Zuuren, Stam, van der Ploeg, Huijgens, et al., only once) and the qualitative studies included 191 participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-efficacy as a psychological resource is associated with better outcomes in most demanding situations and this may partly explain the association we revealed. More specific medical information will give these individuals higher degrees of satisfaction and further reduce their level of anxiety symptoms [41, 49, 50]. …”
Section: Discussionmentioning
confidence: 99%